The Comorbidity of Violence Exposure, Mental Health, Cognitive Functioning, and Disabilities in Incarcerated Youth - Suzanne Perkins; Sriamsha Dubbaka; Erin Wang; Michaela Wu; Wendy Su; Vanessa Assaf; Julianne Park; Joanne Smith-Darden; Sandra Graham-Bermann (Journal of Child & Adolescent Trauma, 2026)
Abstract Objective. The goal of the present study was to ascertain the prevalence rates of violence exposure (VE) and disabilities in a population of incarcerated male adolescents using records searches, survey research, and individual academic and cognitive testing. Methods. A sample of 115 incarcerated male youth completed self-reported measures of VE, including adverse childhood experiences (ACE), child abuse and neglect, interpersonal violence experiences (IPV), and community violence exposure (CV), including current functioning and individual testing of cognition and disability diagnosis (evaluating both features of cognitive and mental health). Results. 90% of participants had experienced at least mild physical abuse, two-thirds reported high ACEs, and one-third reported severe prior sexual abuse (SA) using the CTQ. Over 60% had a prior disability in their records, and over 75% were diagnosable during individual cognitive testing. Just over 50% of youth fit criteria for a mental health diagnosis, and with cognitive disabilities, this prevalence rate increased to 85% of the population. Youth with disabilities had higher rates of VE. Conclusion. Few existing studies analyze combined data related to prior VE, disability diagnosis using individual measures, while testing for current cognitive functioning in incarcerated youth. The present study determined that high rates of disability among incarcerated youth were largely driven by cognitive and academic disabilities, rather than mental health problems, indicating a pervasive problem with cognitive disabilities in this population. Cognitive disabilities, particularly in youth with prior histories of VE, are an intervention point that has the potential to reduce recidivism.